RESPON PERTUMBUHAN DAN HASIL TANAMAN SORGUM LOKAL RARA TADDA TERHADAP PEMBERIAN PUPUK KANDANG SAPI DI LABORATORIUM KANATANG KABUPATEN SUMBA TIMUR - Orija Rambu Baba Nguda, Reri; Danga Lewu, Lusia (Jurnal Biogenerasi, 2024)
Sorghum is an important food crop after rice, corn and wheat. This research aims to analyze the response of growth and yield of local Rara Tadda sorghum plants to the application of cow manure. The method used was a complete randomized experiment with varying doses of cow manure, namely 5, 10, 15 and 20 tons per hectare. The results of this study showed that the application of cow manure significantly increased plant height growth up to 12 WAP with a value of 112.53 cm, treatment with the number of leaves with a value of 14,2500, treatment with panicle length with a value of 45,200 cm, treatment with seed weight per panicle 90.00 grams and seed weight per 1000 grains with a value of 29,000 grams. Cow manure gave no significant difference to the best plant height P4 = 20 tons/ha = 3,080 grams, treatment with the number of leaves obtained the optimal value P4 = 20 tons/ha = 3,080 grams, panicle length treatment P3 = 15 tons/ha = 2,310 grams , seed weight treatment per panicle P0 (control) and seed weight treatment per 1000 grains P3 = 15 tons/ha = 2,310 grams. Apart from that, cow manure also has a positive effect on the growth of sorghum plants. This research concludes that the use of cow manure can increase the productivity of local Rara Tadda sorghum plants.